European Union and the Challenges of Globalization - Florin Bonciu (Romanian Journal of European Affairs, 2006)
The paper analyzes the current implications of globalization on the European Union. While the EU recorded significant successes mainly in the filed of integration and enlargement, the implications of globalization seem rather worrisome. The EU – 15 member countries are facing increased competition from both developed countries and emerging countries like China and India and this fact determines a need for reflection upon the European integration model. Until a solution is found, some companies and countries are tempted to apply protectionist measures which can not be effective in the long run. Looking at the structural causes of the current EU lack of competitivity the paper proposes a solution based on accepting and capitalizing on European diversity.